2019
DOI: 10.1080/22221751.2019.1643260
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E-related adverse pregnancy outcomes and their prevention by hepatitis E vaccine in a rabbit model

Abstract: Hepatitis E virus (HEV) can lead to high mortality during pregnancy. This study was to investigate the adverse pregnancy outcomes caused by different HEV genotypes and their prevention by HEV 239 vaccine in rabbits. Forty-two female rabbits were randomly and equally divided into 7 groups (A-G). HEV 239 vaccine and a placebo were administered to groups E (10 μg×2), F (5 μg×2) and G (1 mL of PBS×2) before copulation. After pregnancy, 1 mL of 1.5×106 copies/mL rabbit HEV3 was inoculated to groups A, E, F and G, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…A study demonstrated that the newborn rabbits delivered by HEV-infected pregnant rabbits showed HEV infection, which indicated vertical transmission of HEV. 31 In modern breeding facilities, rabbits are usually caged individually and separated from their excretions. Therefore, vertical transmission of HEV3-ra in farmed rabbits cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…A study demonstrated that the newborn rabbits delivered by HEV-infected pregnant rabbits showed HEV infection, which indicated vertical transmission of HEV. 31 In modern breeding facilities, rabbits are usually caged individually and separated from their excretions. Therefore, vertical transmission of HEV3-ra in farmed rabbits cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…However, 60% (3/5) of the inoculated rabbits seroconverted to anti-HEV at the end of the study indicating inapparent infection. We previously found that this hHEV-3 strain could induce robust infection in pregnant rabbits [ 32 ]. This observation may be explained by the different host immune status during pregnancy, which increased the host susceptibility to certain pathogens and increased disease severity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum and fecal samples were collected weekly for two consecutive weeks to test alanine aminotransferase (ALT) for establishing the baselines. All samples were negative for anti-HEV antibodies by an enzyme-linked immunosorbent assay (ELISA) and HEV RNA by a previously described reverse transcription-nested polymerase chain reaction (RT-nPCR) [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HEV 239 also seems to be safe in pregnant women [143]. In addition, in a rabbit model, two doses of 10 μg or 5 μg HEV 239 vaccine administered intramuscularly on weeks 0 and 4 not only serve to protect pregnant rabbits from HEV infection but also prevent HEV-related adverse outcomes [144]. Although the safety and efficacy of this vaccine in a large population of pregnant women remain to be determined, this vaccine is promising for HEV infection prevention in pregnancy and may thus decrease HEV-associated morbidity and mortality.…”
Section: Management Of Hev Infection During Pregnancymentioning
confidence: 99%